Magnolol Suppresses TGF-β-Induced Epithelial-to-Mesenchymal Transition in Human Colorectal Cancer Cells - Chei, Sungwoo; Oh, Hyun-Ji; Song, Ji-Hyeon; Seo, Young-Jin; Lee, Kippeum; Lee, Boo-Yong (Frontiers in Oncology, 2019)
Tumor metastasis is the end state of a multistep process that includes dissemination of tumor cells to distant organs and requires tumor cells to adapt to different tissue microenvironments. During metastasis, tumor cells undergo a morphological change known as transdifferentiation or the epithelial-to-mesenchymal transition (EMT). In normal embryonic development, the EMT occurs in the context of morphogenesis in a variety of tissues. Over the course of this process, epithelial cells lose their cell–cell adhesion and polarity properties. In this study, we investigated whether magnolol could suppress the EMT in human colorectal cancer cells. To this end, we examined the epithelial markers E-cadherin, ZO-1, and claudin and the mesenchymal markers N-cadherin, TWIST1, Slug, and Snail. Magnolol effectively inhibited EMT in human colon cancer cell lines by upregulating epithelial markers and downregulating mesenchymal markers. The EMT is induced by the TGF-β signaling pathway. To determine whether magnolol disrupts TGF-β signaling, we examined several mediators of this pathway, and found that magnolol decreased the levels of phosphorylated (i.e., active) ERK, GSK3β, and Smad. We conclude that magnolol blocks migration in HCT116 cells by suppressing TGF-β signaling.